Рынок труда в Польше. Перспективы и проблемы в свете результатов Всеобщей национальной переписи 2002 года - Навойчик, М. (Социология: теория, методы, маркетинг, 2005)
The changes on the Polish labor market are influenced by two processes: 1) the systemic change from socialist toward market economy and 2) globalization. Privatization and restructuring of the socialist economy are the most important factors of the first process. Both of them, from the point of view of the labor market analysis, have disadvantages — such as high unemployment rate and advantages — changes in the occupational status (the emergence of new categories: employers and self employed) and in proportion of the employed within various sectors of the economy (decrease in industry and agriculture; increase in service). All the above mentioned processes connected with systemic transformation are visible through the National Census data. However, these data did not provide any insight to globalization processes. Given occupational classification as well as description of economic activities do not provide basis for analysis of the modern services industry’s emergence.